Cabaran Reformasi Alaf Baru (The Challenge of Reformation in the New Millennium) Series 2 (continuity) - Safei, Su'aidi (Terengganu State Foundation Printing, 1998)
The nature of egoism "Anani" and self interest claims the dignity of the social order and erodes the sense of togetherness. The team spirit or family work must properly be refreshed. Each serves to meet their individual responsibilities with full  dedication and aspirations.